Assessment of needs for counselling after prenatal diagnosis of congenital heart disease: development and evaluation of a questionnaire - Simmelbauer, Andreas; Bär, Stefan; Starystach, Sebastian; Elsässer, Michael; Sohn, Christof; Gorenflo, Matthias; Kovacevic, Alexander; Müller, Andreas (The thoracic and cardiovascular surgeon reports, 2018)
Thieme E-Books & E-Journals
Gesehen am 03.12.2018